Insights into substance abuse knowledge and attitudes among high school students in Anbar Province, Iraq (Journal of Ideas in Health, 2024)
Background: The high prevalence of substance use among children and adolescents has become a major global public health concern. This study aims to explore adolescents' knowledge and attitudes toward substance abuse. Methods: A cross-sectional study was conducted from January 2nd to February 15th, 2023 in Ramadi City, Anbar Province, Iraq. Students from eight high schools participated, selected through a multistage sampling approach. The bivariate analysis included independent sample t-tests and one-way ANOVA. Furthermore, a multivariable linear regression analysis was employed to predict factors influencing knowledge and attitudes. Statistical analyses were performed using SPSS version 16.Results: The study included 415 students, with a mean age of 16.7 (±9.3) years, with a majority being male (52.8%). Accuracy rates for knowledge and attitude were 79.6% and 70.2%, respectively. About 79.3% of participants were familiar with terms related to drug abuse in Iraq. Regression analysis showed that higher knowledge scores were linked with male gender and a household income exceeding IQD 600,000 monthly (95% CI:1.311 to 2.923; P
Keywords: Students, high school, Substance, Drug, Abuse, Knowledge, Attitude, Iraq